INTEGRASI FILSAFAT ILMU DAN NILAI-NILAI AGAMA DALAM MEMBANGUN KARAKTER GEN Z DI TENGAH ARUS MODERNITAS - Ai Silvi Nurhasanah; Ani Rindiani; Ramlan Abdul Wasi’; Nurulhusna Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine in depth the importance of integrating philosophy of science and religious values in shaping the character of Generation Z in the digital age. Amidst the flood of information, technological penetration, and secularization trends, Generation Z faces complex challenges that threaten the balance between their intellectual and spiritual aspects. Philosophy of science contributes to the formation of critical and reflective thinking patterns, while religion provides a moral foundation, meaning of life, and strong spiritual orientation. This study uses a qualitative approach with a literature review method, analyzing various scientific sources to formulate a conceptual framework that synergizes the two approaches. The results of the study indicate that the integration of philosophy of science and religion can produce a generation that is not only academically excellent but also ethically and religiously mature. The implementation strategy for this synergy includes the development of an integrative curriculum, values-based character building, interdisciplinary educator training, and the use of digital media for the dissemination of educational values. With this approach, the educational paradigm can shift from merely transmitting knowledge to forming a holistic and transformative character.